Search for neutrino emission from GRB 221009A using the KM3NeT ARCA and ORCA detectors - Aiello S.; Albert A.; Alshamsi M.; Alves Garre S.; Ambrosone A.; Ameli F.; Andre M.; Androutsou E.; Anguita M.; Aphecetche L.; Ardid M.; Ardid S.; et al. (Journal of Cosmology and Astroparticle Physics, 2024)
Gamma-ray bursts are promising candidate sources of high-energy astrophysical neutrinos. The recent GRB 221009A event, identified as the brightest gamma-ray burst ever detected, provides a unique opportunity to investigate hadronic emissions involving neutrinos. The KM3NeT undersea neutrino detectors participated in the worldwide follow-up effort triggered by the event, searching for neutrino events. In this paper, we summarize subsequent searches, in a wide energy range from MeV up to a few PeVs. No neutrino events are found in any of the searches performed. Upper limits on the neutrino emission associated with GRB 221009A are computed.